1999
DOI: 10.1007/s004320050273
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac troponin T as a marker of myocardial damage caused by antineoplastic drugs in rabbits

Abstract: Anthracycline derivatives are among the most effective antineoplastic drugs but their therapeutic use is limited by their adverse effects. The cardiac side-effects of antineoplastic drugs were investigated in rabbits in vivo from the viewpoint of release of cardiac troponin T (cTnT) measured by Elecsys Troponin T STAT immunoassay (Boehringer Mannheim, Germany). No increase in cTnT was found following administration of a single dose of daunorubicin (3 mg/kg i.v., n = 4). During development of daunorubicin-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 25 publications
2
19
0
1
Order By: Relevance
“…The use of cTnT as a biomarker of doxorubicin cardiotoxicity in animal studies was first reported by Seino et al, in spontaneously hypertensive rats (Seino et al, 1993). Numerous subsequent studies have then confirmed the utility of serum cTnT monitoring to detect the extent of anthracyclineinduced cardiac damage (Herman et al, 1998(Herman et al, ,1999Adamcova et al, 1999;Simunek et al, 2003).…”
Section: Discussionmentioning
confidence: 90%
“…The use of cTnT as a biomarker of doxorubicin cardiotoxicity in animal studies was first reported by Seino et al, in spontaneously hypertensive rats (Seino et al, 1993). Numerous subsequent studies have then confirmed the utility of serum cTnT monitoring to detect the extent of anthracyclineinduced cardiac damage (Herman et al, 1998(Herman et al, ,1999Adamcova et al, 1999;Simunek et al, 2003).…”
Section: Discussionmentioning
confidence: 90%
“…In the first cycle, we sought to determine whether a single clinically relevant dose of ANT can induce a significant cTn release and whether this may identify animals with a higher future cardiotoxicity risk. We performed the same analysis after five ANT cycles (~250 mg/m 2 ), when we previously found the first significant cTn elevation while cardiac function was still normal [10,15]. Eight cycles were then used as the interval in which the first significant drop of LV systolic function appears in this model.…”
Section: Discussionmentioning
confidence: 99%
“…Scattered data in the literature, including our own [15][16][17], has suggested that ANT-induced cardiac damage is associated with a relatively prolonged release of cTns, but further details are lacking. A significant increase of cTns after ANT exposure has also been found in numerous clinical studies (reviewed in [18]).…”
Section: Introductionmentioning
confidence: 94%
“…As shown in figure 1 , the administration of 5-ALA is associated with the appearance of both c-Tn I and CK. We and other authors have previously detected these markers in rabbit plasma [31,32] , which can be done using antibodies against human c-Tn I because the peptide sequences in human and rabbit cardiac troponins are highly similar or identical [33][34][35] and allow the cross-reactivity reactions observed in various species [36,37] .…”
Section: Discussionmentioning
confidence: 99%